2022
DOI: 10.1186/s43058-022-00291-5
|View full text |Cite
|
Sign up to set email alerts
|

Brief physical activity counselling by physiotherapists (BEHAVIOUR): protocol for an effectiveness-implementation hybrid type II cluster randomised controlled trial

Abstract: Background Physical inactivity is a leading risk factor for chronic disease. Brief physical activity counselling delivered within healthcare systems has been shown to increase physical activity levels; however, implementation efforts have mostly targeted primary healthcare and uptake has been sub-optimal. The Brief Physical Activity Counselling by Physiotherapists (BEHAVIOUR) trial aims to address this evidence-practice gap by evaluating (i) the effectiveness of a multi-faceted implementation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(73 reference statements)
2
2
0
Order By: Relevance
“…This result is consistent with other studies which have found that physiotherapists, across diverse healthcare settings (e.g., general practice, cancer care), have expertise and knowledge in PA promotion and typically integrated some form of discussion about activity with their patients (Albert et al 2020;Hassett et al 2022). Physiotherapists agree that PA promotion should be part of their clinical role (Aweto et al 2013;Freene et al 2017;Hassett et al 2022;Mouton et al 2014;Shirley et al 2010). Our qualitative findings confirm those of previous research; yet, participants in our study felt that all members of the MDT should prioritize and take an active role in encouraging patients to move more.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with other studies which have found that physiotherapists, across diverse healthcare settings (e.g., general practice, cancer care), have expertise and knowledge in PA promotion and typically integrated some form of discussion about activity with their patients (Albert et al 2020;Hassett et al 2022). Physiotherapists agree that PA promotion should be part of their clinical role (Aweto et al 2013;Freene et al 2017;Hassett et al 2022;Mouton et al 2014;Shirley et al 2010). Our qualitative findings confirm those of previous research; yet, participants in our study felt that all members of the MDT should prioritize and take an active role in encouraging patients to move more.…”
Section: Discussionsupporting
confidence: 91%
“…Survey results showed that 85% of physiotherapists delivered sessions to patients. This result is consistent with other studies which have found that physiotherapists, across diverse healthcare settings (e.g., general practice, cancer care), have expertise and knowledge in PA promotion and typically integrated some form of discussion about activity with their patients (Albert et al 2020;Hassett et al 2022). Physiotherapists agree that PA promotion should be part of their clinical role (Aweto et al 2013;Freene et al 2017;Hassett et al 2022;Mouton et al 2014;Shirley et al 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this instance, effectiveness data may be yielding lower outcome change than in efficacy trials, so a closer examination of implementation strategy or strategies is necessary. A Type II hybrid design would be appropriate if there is strong evidence for both the intervention itself as well as strong evidence for the implementation strategy being studied, but the two components are being applied in a novel way—such as in a new population and/or are being studied together for the first time (Hassett et al, 2022 ).…”
Section: Basics Of and Rationale For Hybrid Effectiveness-implementat...mentioning
confidence: 99%
“…Physiotherapy is a service provided solely by or under the direction and supervision of an accredited physiotherapist, through a degree and professional certificate, which enable him to manage the Intervention Model in Physiotherapy which includes: examination, assessment, diagnosis, prognosis, intervention or treatment plan and reassessment. Physiotherapy deals with potentiating and maximizing quality of life, identifying, and treating movement disorders within the areas of promotion, prevention, treatment and/or intervention, habilitation and rehabilitation (Hassett et al, 2022).…”
Section: Introductionmentioning
confidence: 99%